Review and comparison of experimental techniques used for determination of thin film electro‐optic coefficients. Issue 9 (29th April 2015) - Nitiss, Edgars; Bundulis, Arturs; Tokmakov, Andrejs; Busenbergs, Janis; Linina, Elza; Rutkis, Martins
Abstract : The results of electro‐optic coefficient measurements performed with three commonly applied techniques used to assess electro‐optic coefficients: the Mach–Zehnder, the Teng–Man, and the attenuated total reflectance technique are reported. It is shown that the signal obtained by the Mach–Zehnder and Teng–Man techniques is strongly influenced by the multiple internal reflection and piezo‐ and electrostrictive thickness change effects, which in our opinion have not been addressed sufficiently in the literature. A novel approach based on using Abelès matrix formalism is implemented for the retrieval of electro‐optic coefficients from experimental data. The measurement results, errors, and comparison of the obtained electro‐optic coefficient values with the ones expected from the second harmonic generation measurements are discussed. It is demonstrated that, by applying incidence angle scan measurements in Teng–Man technique, an analytic approximation that ignores multiple internal reflection and thickness change effects can provide an electro‐optic coefficient estimate within the precision of 2%. This value is much less than the error caused by the thickness change effect that may appear in the attenuated total reflectance technique which inherently has low sensitivity to the thickness modulation effects in the sample. Abstract : The authors report the results of electro‐optic coefficient measurements performed with three commonly applied techniques used to assess electro‐optic coefficients: the Mach‐Zehnder, the Teng‐Man and the attenuated total reflectance technique. As shown, the correct interpretation of the experimental data obtained by the mentioned techniques requires the full understanding of the effects taking place in the sample.